Gingiva-Derived Mesenchymal Stem Cells Attenuate Imiquimod- (IMQ-) Induced Murine Psoriasis-Like Skin Inflammation. (30th June 2022) - Ye, Ziyu; Liang, Yanfang; Lin, Bihua; Li, Yanyun; Chai, Xingxing; Lian, Jiachun; Zhang, Xueying; Che, Zhengping; Zeng, Jincheng
Abstract : Human gingiva-derived mesenchymal stem cells (GMSCs) are isolated from the gingival propria with promising regenerative, immunomodulatory, and anti-inflammatory properties. Recently, several studies, including ours, have found that GMSCs have the therapeutic potentials of nerve regeneration and skin disorders in various types such as the cell itself, cell-free conditioned medium, or extracellular vesicles (EVs). However, the mechanobiological behavior of GMSCs is closely related to the culture conditions. Therefore, the purpose of this study was to evaluate the function of human GMSCs on imiquimod- (IMQ-) induced murine psoriasis-like skin inflammation in two-dimensional (2D) and three-dimensional (3D) culture conditions. Here, we isolated and characterized GMSCs in 2D and 3D culture conditions and found that GMSCs in 2D and 3D infusion can significantly ameliorate the IMQ-induced murine psoriasis-like skin inflammation, reduce the levels of Th1- and Th17-related cytokines IFN- γ, TNF- α, IL-6, IL-17A, IL-17F, IL-21, and IL-22, and upregulate the percentage of spleen CD25 + CD3 + T cells while downregulate the percentage of spleen IL-17 + CD3 + T cells. In summary, our novel findings reveal that GMSCs in 2D and 3D infusion may possess therapeutic effects in the treatment of psoriasis.